2012
DOI: 10.1111/j.1365-2958.2012.08206.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the type VII secretion system membrane complex

Abstract: SummaryPathogenic mycobacteria require type VII secretion (T7S) systems to transport virulence factors across their complex cell envelope. These bacteria have up to five of these systems, termed ESX-1 to ESX-5. Here, we show that ESX-5 of Mycobacterium tuberculosis mediates the secretion of EsxN, PPE and PE_PGRS proteins, indicating that ESX-5 is a major secretion pathway in this important pathogen. Using the ESX-5 system of Mycobacterium marinum and Mycobacterium bovis BCG as a model, we have purified and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
204
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(222 citation statements)
references
References 51 publications
11
204
4
3
Order By: Relevance
“…This satisfies earlier studies showing that the membrane-extrinsic region of EccC is monomeric when crystallised 8 and is in agreement with the findings of Beckham et al 5 that this region of EccC can adopt multiple conformations in single particles, suggesting this region is highly flexible in the resting state. Upon substrate binding the ATPase domains of EccC could then oligomerize 8 , and modelling a multimer of the ATPase domains of EssC (from the distantly-related T7 secretion system of Gram-positive firmicutes) suggests that this would form a channel inside the hexamer of approximately 30 Å 9 .…”
Section: Main Text (800-900 Words)supporting
confidence: 81%
See 2 more Smart Citations
“…This satisfies earlier studies showing that the membrane-extrinsic region of EccC is monomeric when crystallised 8 and is in agreement with the findings of Beckham et al 5 that this region of EccC can adopt multiple conformations in single particles, suggesting this region is highly flexible in the resting state. Upon substrate binding the ATPase domains of EccC could then oligomerize 8 , and modelling a multimer of the ATPase domains of EssC (from the distantly-related T7 secretion system of Gram-positive firmicutes) suggests that this would form a channel inside the hexamer of approximately 30 Å 9 .…”
Section: Main Text (800-900 Words)supporting
confidence: 81%
“…Further periplasmic density was contributed by EccE which was shown to be located at the periphery of the complex. This careful mapping of individual components within the structure allowed Beckham et al 5 to propose an overall organisation for the secretion machinery where the EccC-EccB-EccD-EccE proteins essentially form four concentric hexameric rings. The structure provides a framework for the design of experiments to assess the roles of individual components within the complex, and to propose models to describe how protein secretion is achieved.…”
Section: Main Text (800-900 Words)mentioning
confidence: 99%
See 1 more Smart Citation
“…ESX-1 is partially missing in the vaccine strain Mycobacterium bovis Bacille Calmette-Guérin [32], indicating a contribution to virulence. Previous investigations have demonstrated a crucial role of T7SS in bacterial survival within the host [21,23,31,32], consistent with transmission electron micrographs of interactions between S. iniae DX09 and spleen cells from diseased catfish. Moreover, considerable evidence is available supporting essential roles of the actinobacterial ESS protein secretion system in virulence [26][27][28][29].…”
Section: Iusa1 and Sf1supporting
confidence: 51%
“…We have identified an ESS secretion system in S. iniae, which also belongs to the low-GC Firmicutes bacterial group. Pathogenic mycobacteria generally possess up to five different T7SS (ESX-1, ESX-2, ESX-3, ESX-4 and ESX-5), which have possibly evolved via gene duplication [31]. Several studies suggest that ESX-1, the first T7SS identified, strongly influences host-pathogen interactions, in particular, the ability of bacteria to escape the phago-vacuole of infected cells (macrophages and dendritic cells) [23].…”
Section: Iusa1 and Sf1mentioning
confidence: 99%